Phenolic profile and antioxidant, anticholinesterase and anti- candida potential evaluation in vitro and in silico studies of Tapirira guianensis Aubl. extracts (Research, Society and Development, 2022)
Polar extracts of Tapirira guianensis Aubl. were prepared for evaluation of biological activities. Identification and quantification of phenolic compounds, antioxidant activity, inhibition of acetylcholinesterase enzyme and antifungal potential were performed in all extracts. High contents of total phenols were detected in the ethanolic and aqueous extracts of the leaves (237.10±5.39 mg EAG/g and 346.46±5.67 mg EAG) respectively. The same extracts had a free radical scavenging potential by both DPPH and ABTS+ methods. Ethanolic extract of the leaves with IC50= 15.06±0.02 µg/mL and 16.49±0.01µg/mL) and aqueous extracts (11.54±0.01 µg/mL and 15.14±0.02 µg/mL respectively. In the study by high-performance liquid chromatography the phenolic substances were recorded: gallic acid, rutin, ellagic acid, quercetin and apigenin in the leaves and gallic acid and quercetin in the stem bark. Ethanolic and aqueous extracts of the leaves and stem bark showed high potency of inhibiting the enzyme acetylcholinesterase, with IC50 values = 13.94±0.02 µg/mL, 13.69±0.08 µg/mL and 14.79±0.20 µg/mL respectively. The aqueous extract of the leaves showed anti-Candida action against all four strains of the microorganism. The in silico studies evidenced that all the ligands analyzed presented interaction with the SAP5 protein highlighting the ellagic acid, the rutin and the quercetin. With these results, the activities previously reported for the species T. guianensis are confirmed, highlighting the polar extracts, mainly aqueous as a source of antioxidant, acetylcholinesterase inhibitor and antifungal substances.